Can environmental pollution by metals change genetic diversity? Ucides cordatus (Linnaeus, 1763) as a study case in Southeastern Brazilian mangroves - Banci, Karina Rodrigues da Silva; Mori, Gustavo Maruyama [UNESP]; Oliveira, Marcos Antonio de [UNESP]; Paganelli, Fernanda Laroza; Pereira, Mariana Rangel; Pinheiro, Marcelo Antonio Amaro [UNESP] (Elsevier, 2017)
Industrial areas on estuarine systems are commonly affected by heavy metals, affecting all local biota. Random Amplified Polymorphic DNA (RAPD) was used to evaluate genetic diversity of Ucides cordatus at mangroves in southeastern Brazil (Jurï¿½ia, J; Sï¿½o Vicente, SV; and Cubatï¿½o, C), with distinct pollution levels by metals. The genetic diversity of this species was compared with concentrations of metals (Cd, Pb, Cu, Cr and Hg) in the environment. A pollution gradient was confirmed (SVï¿½>ï¿½Cï¿½>ï¿½J), with low levels detected in water, except for mercury in SV. All metals in the sediment samples were below Threshold Effect Level (TEL), without an apparent biological risk to the biota. Genetic distance was very similar between J and C, with SV occurring as an out-group. RAPD was a powerful tool to investigate the effect of metal pollution on genetic diversity of this mangrove crab, and to evaluate the conservation status of the mangrove ecosystem.
Keywords: Biomonitoring; Conservation; Crab; Estuary; Metals; Pollution